ESG systems and financial performance in industries with significant environmental impact: a comprehensive analysis - Li, Qingwen; Tang, Waifan; Li, Zhaobin (Frontiers in Sustainability, 2024)
Research Background and Significance：As China's economy continues its rapid expansion, the issue of environmental degradation has escalated, particularly within industries with significant environmental impact, such as steel, chemical, pharmaceutical sectors. These sectors are confronted with profound environmental and social responsibility challenges. The development of robust Environmental, Social, and Governance (ESG) systems has therefore become essential for improving environmental performance, meeting social responsibilities, and optimizing corporate governance structures. This study investigates the impact of ESG system implementation on the financial performance of enterprises within these environmentally impactful industries, offering a scientific foundation and practical guidance for corporate leaders and policymakers to facilitate green transformation and sustainable development.Methods and Data：This research integrates empirical analysis with case studies, employing a dataset of 2,376 observations from 792 listed companies within industries with significant environmental impact, spanning the period from 2019 to 2021. The data, sourced from the Wind database, were analyzed using multiple regression techniques. The findings reveal a significant positive relationship between overall ESG scores and corporate performance, measured by Return on Equity (ROE) and Return on Assets (ROA). All three ESG dimensions-environmental (E), social (S), and governance (G)-exhibit positive impacts on corporate performance. Furthermore, factors such as company size and growth rate are positively correlated with performance, whereas leverage ratio is negatively correlated. To further substantiate the empirical findings, a case study of Hunan Valin Steel Co., Ltd. was conducted.The findings of this study demonstrate that the implementation of ESG systems substantially enhances the financial performance of enterprises within industries characterized by significant environmental impacts. Specifically, investments in environmental protection led to greater resource utilization efficiency, social responsibility initiatives foster enhanced employee productivity and customer loyalty, and strong corporate governance improves management structures and decision-making processes. The case study of Hunan Valin Steel Co., Ltd. reinforces these results, illustrating that a comprehensive ESG framework not only helps such enterprises achieve their environmental and social responsibility objectives but also markedly improves their financial outcomes. This research provides robust empirical evidence and actionable management recommendations for ESG system implementation in environmentally impactful industries, along with scientific support for informed policymaking.